Local Administration of Ginkgolide B Using a Hyaluronan-Based Hydrogel Improves Wound Healing in Diabetic Mice - Wang, Limei; Xia, Kedi; Han, Lu; Zhang, Min; Fan, Jihuan; Song, Liu; Liao, Anqi; Wang, Wenyu; Guo, Jianfeng (Frontiers in Bioengineering and Biotechnology, 2022)
The delayed and incomplete healing of diabetic wounds remains a major concern of global healthcare. The complex biological processes within the diabetic wound, such as chronic inflammation, impaired blood vessel growth and immature collagen remodeling, dramatically cause the failure of current treatments. Thus, emerging therapeutic strategies are highly desirable. Ginkgolide B (GB, a natural product extracted from the leaves of Ginkgo biloba L.) has been applied in the treatment of cerebrovascular and cardiovascular disorders, which is mainly due to the anti-oxidative, anti-inflammatory and proliferative effects. In this study, the role of GB in facilitating the anti-inflammatory and pro-healing effects on diabetic wounds was for the first time confirmed using in vitro, ex vivo and in vivo experimental methods. As a consequence, GB was able to significantly achieve the activities of anti-inflammation, re-epithelialization, and pro-angiogenesis. Previously, a hydrogel has been developed using the high molecular weight hyaluronan (hyaluronic acid, HA) in our laboratory. In this study, this hydrogel was utilized in vivo for local administration of GB to the full-thickness wounds of diabetic mice. The resultant hydrogel formulation (HA-GB) resulted in the reduction of inflammation, the enhancement of re-epithelialization and angiogenesis, and the modulation of collagens from type III to type I, significantly promoting the healing outcome as compared with a commercially available wound dressing product (INTRASITE Gel). This study confirms a great therapeutic promise of HA-GB for the chronic wounds of diabetic patients.